Evolving evidence in the treatment of primary and recurrent posterior cruciate ligament injuries, part 2: surgical techniques, outcomes and rehabilitation - Winkler, Philipp W. (Knee Surg Sports Traumatol Arthrosc, 2020)
ABSTRACT: Isolated and combined posterior cruciate ligament (PCL) injuries are associated with severe limitations in daily, professional, and sports activities as well as with devastating long-term effects for the knee joint. As the number of primary and recurrent PCL injuries increases, so does the body of literature, with high-quality evidence evolving in recent years. However, the debate about the ideal treatment approach such as; operative vs. non-operative; single-bundle vs. double-bundle reconstruction; transtibial vs. tibial inlay technique, continues. Ultimately, the goal in the treatment of PCL injuries is restoring native knee kinematics and preventing residual posterior and combined rotatory knee laxity through an individualized approach. Certain demographic, anatomical, and surgical risk factors for failures in operative treatment have been identified. Failures after PCL reconstruction are increasing, confronting the treating surgeon with challenges including the need for revision PCL reconstruction. Part 2 of the evidence-based update on the management of primary and recurrent PCL injuries will summarize the outcomes of operative and non-operative treatment including indications, surgical techniques, complications, and risk factors for recurrent PCL deficiency. This paper aims to support surgeons in decision-making for the treatment of PCL injuries by systematically evaluating underlying risk factors, thus preventing postoperative complications and recurrent knee laxity. LEVEL OF EVIDENCE: V.